KOMBINASI FEED BACK DAN FEED FORWARD KONTROLLER PI SEBAGAI KENDALI DYNAMIC VOLTAGE RESTORER (DVR) UNTUK MEMULIHKAN VOLTAGE SAG DAN INTERRUPTION - Dimas Anton A; Imron Rosyadi; Mochamad Ashari; Heri Suryoatmojo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
Dynamic voltage restorer (DVR) is one of equipments to protect sensitive load from voltage drop. DVR is installed series with line feeder by serial transformer which injecting voltage when under voltage occurs. This research is investigate the capability of DVR, which controlled by combination of feed back and feed forward PI, to handle voltage sag and interruption. DVR controls have been designed and implemented in DVR prototype. As a result, in simulation, DVR can maintain voltage in range 90% - 105% nominal voltage. Voltage at load side can be restored to 1 pu and 0.79 pu when voltage sag and interruption respectively. Furthermore, DVR prototype can restore 0.95 pu when voltage sag and 0.54 pu when interruption.